Graphs Generated by Measures - A. Assari; M. Rahimi (Journal of Mathematics)
In this paper, a graph is assigned to any probability measure on the σ-algebra of Borel sets of a topological space. Using this construction, it is proved that given any number n (finite or infinite) there exists a nonregular graph such that its clique, chromatic, and dominating number equals n.